Elimination of ineffective inorganic salt component in medium for indole‐3‐acetic acid synthesis by Serratia plymuthica UBCF_13 and its effect on the growth of chili seedlings - Liza Aulia Yusfi; Djong Hon Tjong; Irawati Chaniago; Muhamad Irsyad; Jamsari Jamsari (Indonesian Journal of Biotechnology, 2024)
Indole‐3‐acetic acid (IAA) is an essential phytohormone that controls a variety of plant growth mechanisms. Bacteria can produce IAA to stimulate plant growth, with its production influenced by the culture conditions. Serratia plymuthica UBCF_13 is recognized as an IAA‐producing bacterium, exhibiting maximum IAA production in a yeast medium comprising yeast extract, sucrose, K2HPO4, MgSO4, NaCl, and CaCO3. However, prior studies optimizing individual inorganic salt components indicated minimal impact on IAA synthesis within this medium. This study aimed to eliminate the unnecessary inorganic salt components and the medium was then applied to investigate the IAA biosynthesis pathway and the plant growth‐promoting assay. The elimination assay consisted of yeast sucrose medium devoid of K2HPO4, MgSO4, NaCl, or CaCO3, and yeast sucrose medium containing only MgSO4 and CaCO3. Various indole compounds were then added to the revised medium composition to investigate the IAA biosynthesis pathway of UBCF_13 using high‐performance liquid chromatography (HPLC). Furthermore, the effect of UBCF_13 culture supernatant, cultivated in the new medium, on chili plant growth was evaluated. The highest IAA production (138.8 µg/mL) was observed in the yeast sucrose with CaCO3 and MgSO4 (elimination of K2HPO4 and NaCl). The presence of indole‐3‐acetamide (IAM) compound from the medium extracts, supplemented with multiple indole compounds, revealed that UBCF_13 may use the IAM pathway. The application of UBCF_13 supernatant enhanced the shoot, root length, fresh weight, and germination time of chili seeds by 37.7%, 49.3%, 204.3%, and 38.6%, respectively. This study demonstrated that eliminating K2HPO4 and NaCl provided a new culture medium composition conducive to IAA production by UBCF_13. Moreover, the UBCF_13 extract has the potential to promote plant growth.